Mastering the Semi-Structured Interview and Beyond: From Research Design to Analysis and Publication - Galletta, Anne (Qualitative studies in psychology, 2013)
Mastering the Semi-Structured Interview and Beyondoffers an in-depth and captivating step-by-step guide to the use of semi-structured interviews in qualitative research. By tracing the life of an actual research project-an exploration of a school district's effort over 40 years to address racial equality-as a consistent example threaded across the volume, Anne Galletta shows in concrete terms how readers can approach the planning and execution of their own new research endeavor, and illuminates unexpected real-life challenges they may confront and how to address them.The volume offers a close look at the inductive nature of qualitative research, the use of researcher reflexivity, and the systematic and iterative steps involved in data collection, analysis, and interpretation. It offers guidance on how to develop an interview protocol, including the arrangement of questions and ways to evoke analytically rich data.Particularly useful for those who may be familiar with qualitative research but have not yet conducted a qualitative study,Mastering the Semi-Structured Interview and Beyondwill serve both undergraduate and graduate students as well as more advanced scholars seeking to incorporate this key methodological approach into their repertoire.Anne Gallettais Associate Professor at the College of Education and Human Services at Cleveland State University.William E. Cross, Jr.is the author of Shades of Black: Diversity in African-American Identity.In theQualitative Studies in Psychologyseries